Republic of Uzbekistan : Strengthening Fiscal Transparency. (IMF Staff Country Reports; Country Report ;, 2019)
This paper on the Republic of Uzbekistan focuses on the fiscal transparency in the country. This report provides further guidance to support implementation of the fiscal transparency evaluation recommendations and the government's plans to strengthen transparency. The IMF team worked with the authorities to further strengthen the application of the Government Finance Statistics Manual standards, improve the budget classification, presentation and reporting; strengthen fiscal risk disclosure and address other fiscal transparency-related issues. Steps have been taken to improve the coverage of Government Finance Statistics reports; however, further work is required. Wide-ranging reforms to improve the coverage, reliability, quality and accessibility of fiscal reports are being developed. A Presidential Decree, approved in August 2018, sets out measures to enhance budget openness and transparency, increase the engagement of citizens in the budget process, and strengthen parliamentary and public scrutiny of the budget.